Theileria annulata Cyclophilin1 (TaCyp1) Interacts With Host Cell MED21 - Zhao, Shuaiyang (Front Microbiol, 2018)
Host cells infected by Theileria annulata schizonts show the character of permanent proliferation in vitro, also named transformation. To explore the molecular mechanism a T. annulata Cyp1 (TaCyp1) protein potentially involved in regulating cell transformation was used as bait to screen for its interacting proteins by yeast-two-hybrid assay. Additional GST-pull down experiments confirmed that only MED21 specifically interacted with TaCyp1. Moreover, the distribution of TaCyp1 around T. annulata schizonts facilitated interaction with host cell MED21. As a component of mediator complex, MED21 is normally involved in regulating the transcription of nearly all RNA polymerase II-dependent genes. Therefore, to explore its influence on NF-κB signaling MED21 RNA interference and parasite killing with BW720c treatment were performed. Knock down of MED21 resulted in a significant decrease in NF-κB1/2 mRNA expressions, but no significant change in P105, P52 levels, nor detectable alteration in levels of phosphorylated IκBα/β. By contrast, BW720c treatment induced an obvious decrease in the phosphorylation status of P52 and IκBα/β, but no obvious change in that of P105. This suggests that BW720c-induced parasite death had a significant negative influence on NF-κB signaling, whereas knock down of MED21 had no obvious effect on NF-κB signaling. Characterization of TaCyp1 provides information on the function of parasite cyclophilins and leads to a better understanding of the interactions between T. annulata and its host leukocytes.